Characteristics, composition, and antioxidant activities in vitro and in vivo of Gynostemma pentaphyllum (Thunb.) Makino seed oil. (4th October 2016) - Wang, Lu; Pang, Min; Wang, Xiaobing; Wang, Pan; Xiao, Yaping; Liu, Quanhong
Abstract: BACKGROUND: In order to further develop and utilise Gynostemma pentaphyllum (Thunb.) Makino seeds, a detailed analysis of the characteristics of G. pentaphyllum seed oil (GPSO), including its physico‐chemical parameters, fatty acid composition and unsaponifiable matter constituents, has been investigated in this study. The antioxidant potential of GPSO was evaluated by radical‐scavenging activity and ferric‐reducing antioxidant power assay in vitro, and the antioxidant activity in vivo was examined by using an aged mice model. RESULTS: The main components of the seeds are lipids (485.54 g kg −1 ) and proteins (203.26 g kg −1 ). The GPSO obtained by supercritical CO2 fluid extraction was rich in polyunsaturated fatty acids (92.85%), especially conjugated linolenic acid (88.17%); and various useful compounds (squalene, tocopherol and phytosterols) were identified in the unsaponifiable matter. The overall antioxidant capacity of GPSO in vitro was shown to be comparable to that of Camellia seed oil as a positive control. GPSO could provide protection to the aged mice against oxidative stress and minimised the impact of ageing. CONCLUSION: All the results suggest that GPSO has direct and potent antioxidant activities; it could be utilised as a functional food to supplement or replace some conventional oils. © 2016 Society of Chemical Industry